THE ROLE OF ISLAMIC RELIGIOUS EDUCATION IN ADDRESSING PHUBBING BEHAVIOR AMONG STUDENTS IN GENERAL HIGHER EDUCATION INSTITUTIONS - Nurhilaliyah; Nurbaeti (Teladan: Jurnal Pendidikan Umum dan Karakter, 2026)
The rapid development of digital technology and the intensive use of smartphones among university students have contributed to the emergence of phubbing, namely the act of ignoring direct social interaction because of excessive attention to mobile devices. This behavior weakens interpersonal communication, learning concentration, academic engagement, and ethical awareness in higher education settings. This study aims to analyze the role of Islamic Religious Education, known in Indonesia as Pendidikan Agama Islam or PAI, in addressing phubbing behavior among students in general higher education institutions. The study used a qualitative library research design by examining scholarly literature on phubbing, digital distraction, Islamic character education, digital ethics, and learning interaction. The data were analyzed descriptively through thematic categorization, interpretation, and synthesis. The findings indicate that phubbing among students is shaped by smartphone dependency, weak self-control, permissive peer culture, and insufficient digital ethics. Islamic Religious Education can respond to this problem by strengthening moral consciousness, self-control, exemplary conduct, respectful communication, and responsible technology use. The study argues that PAI will only be effective if it moves beyond normative instruction and is implemented through interactive pedagogy, lecturer role modeling, explicit digital ethics, and institutional policies that support ethical classroom interaction. The study contributes a conceptual IMRAD-based synthesis of PAI as a character education framework for reducing phubbing in contemporary higher education.